Soluble acetylenic molecular glasses based on dithienyldiketopyrrolopyrrole for organic solar cells. (March 2016) - Xia, Yan; Tan, Wan-Yi; Wang, Li-Ping; Zhang, Chun-Hui; Peng, Ling; Zhu, Xu-Hui; Peng, Junbiao; Cao, Yong
Abstract: We present the synthesis and photovoltaic response of soluble glass-forming molecules containing a dithienyldiketopyrrolopyrrole core and difluorenylarylamine endgroups, linked through an acetylene bond. Introducing the 2, 6-naphthylene moiety vs. 1, 4-phenylene leads to an increased glass transition temperature ( T g ) and hole mobility. Thus, T g  = 107.7 °C, μ h  = 7.95 × 10 −5  cm 2  V −1  s −1 for the 1, 4- phenylene compound, while T g  = 119.4 °C, μ h  = 9.17 × 10 −5  cm 2  V −1  s −1 for the 2, 6-naphthylene compound. Thermal annealing the as-cast films of both compounds below T g resulted in little change in optical absorption. The preliminary characterization of the bulk hetero-junction solar cells showed that the 2, 6-naphthylene compound generally provides a higher power conversion efficiency than the 1, 4-phenylene compound, due probably to its enhanced hole transport. The photoluminescence experiments show a weak exciplex emission around 880 nm for the blends containing the new dyes and PC61 BM. The present work may be useful for further efforts toward high-performance cost-effective acetylenic organic semiconductors for organic solar cells with thermally stable morphology. Graphical abstract: Introducing the 2, 6-naphthyl moiety vs. 1, 4-phenyl increases T g and hole mobility, thus contributing to enhancing the power conversion efficiency. Highlights: Soluble acetylenic molecular glasses based onDT-DPP for OSCs have been reported. The optical absorption of the dye films was little affected by thermal annealing below T g . The difluorenyl(2-naphthyl)amine endgroup contributes to increasing μ hole and PCE.